EFFECT OF SALICYLIC ACID ON THE ACTIVITY OF ENZYMATIC ANTIOXIDANTS AND PROLINE IN VEGETATIVE GROWTH OF MAIZE PLANT UNDER NaCl STRESS - Ibrahim, Ismail Khalil; Hamid , Zakaria Hassan (Diyala Agricultural Sciences Journal, 2015)
To study the effect of different levels of salicylic acid on the activity of enzymatic antioxidants and proline in the vegetative growth of maize plant under NaCl stress . A pot experiment was carried out in the greenhouse of the Department of Soil Sciences and Water Resources in the College of Agriculture, University of Baghdad in a silt clay loam soil classified as Typic Torrifluvent . A factorial experiment based on a Randomized Complete Block Design ( RCBD) with three replicates was used . Treatments consisted of three salinity levels (0.5, 5.0, 9.5 dS m-1) and five salicylic acid concentrations ( 0,250,500,1000,1500) µM SA . Results showed significant increase in SOD , POD,CAT activity and proline concentration with the increasing of salinity levels . Foliar applications of salicylic acid significantly reduced the activity of antioxidant enzymes ( SOD, POD,CAT) and proline concentration in Maize plants leaves